PRESTASI AKADEMIK ANAK PANTI ASUHAN PUTERA MUHAMMADIYAH BANGKINANG KOTA - Ayuningtyas, Elna Reviyan; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Academic achievement is the result of the final achievement of learning within a specified period of time through tests that have been provided by each school or institution. Orphanages are institutions or places to accommodate orphans, neglected and under the poverty line. Where children are provided with education and various skills according to the interests and talents of each individual. Putera Muhammadiyah Orphanage is an orphanage built to accommodate orphaned, abandoned children and children under the poverty line. This study aims to determine the factors that influence academic achievement and how the academic achievement of the children at the Putera Muhammadiyah orphanage, Bangkinang city. In this study, the research method used was a quantitative approach with a sample of 40 children. Determination of the subject in this study using census techniques or saturated sampling. The theory used in this research is the structural functionalism theory of Talcott Parsons' adaptation, goal, integration, and latent patent maintenance. From the results of this study, it can be concluded that the academic achievement of the children of Putera Muhammadiyah orphanage in Bangkinang city is in the high category with a percentage of 52.5%. The level of achievement can be divided into two forms. First, level of achievement based on length of stay. Second, the level of achievement based on the child's age. The level of academic achievement based on length of stay shows that more children live more than 3 years. Then, based on the child's age, at the age of 15 the child contribute more to academic achievement.Keywords : Academic Achievement, Orphanage.